Simulation Study of Prostate Tissue Ablation by Pulsed Nd:YAG, Ho:YAG and Thulium Fiber Surgical Lasers with Minimum Carbonization Effect - Dawood, Munqith S.; Monaf, Haider (Nahrain University College of Engineering Journal, 2016)
The laser-tissue interaction and its thermal effects depend on the parameters of both of the tissue and the used laser. In this paper the laser ablation efficiency of prostate tissue has been studied theoretically by using pulsed Nd:YAG, Ho:YAG and Thulium fiber surgical lasers. Different levels of energies were considered for these lasers, which operate in 20 and 40 Hz pulse repetition frequencies (prf) to evaluate the prostate tissue temperature rise up to the required ablation state. The Gambit program was used first to simulate the geometrical shape of the treated prostate tissue, then the radiative transfer equation (RTE) of the ANSYS Fluent program was applied to simulate and solve the ablation process equations. The results showed that the low rates of repetition frequencies and low laser energies increase the allowed time for safe ablation operation before reaching the carbonization state. It was found also that although the Ho:YAG laser vaporizes prostate tissue faster than the Thulium fiber laser did, the pulsed Thulium fiber laser produced much lower temperature side effects like coagulation, hyperthermia and carbonization of the rest of the prostate tissue, which is surrounding the ablated zone for the same applied average powers by the other two lasers.Keywords: ; ; ; ; ; .